Reactions of lithium and magnesium derivatives of substituted o- and m-carboranes with 3-ethoxycoumarin and coumarin - Kazantsev, A. V.; Otrashchenkov, E. A.; Aksartov, M. M.; Turdybekov, K. M.; Yamovoi, V. I.; Adekenov, S. M. (Nauka/Interperiodica, 2002)
Reactions of lithium and magnesium derivatives of substituted o- and m-carboranes with 3-ethoxycarbonylcoumarin and coumarin were investigated. The main directions and the laws of the processes were revealed.